La sobreprotección de marcas notoriamente conocidas: análisis crítico del caso McDonald’s vs McHotel Ica - García Enríquez, Jonathan Rafael (2025)
This article analyzes the legal foundation of the Indecopi's decisions in the case of McDonald’s vs. McHotel Ica, evaluating its impact on the protection of well-known trademarks and competition in the Peruvian market. A qualitative approach is used to examine the arguments of both parties and the justifications for the decisions in the first and second instances. Resolutions from Indecopi, cases from the Andean Tribunal, and relevant regulations such as Decision 486 of the Andean Community and Legislative Decree 1075 are reviewed. The conclusion highlights that the protection of well-known trademarks must be balanced to avoid overprotection that limits competition. The McDonald’s vs. McHotel Ica case underscores the importance of establishing limits on trademark protection and the need for consistent criteria in Indecopi's decisions to promote a fair competitive environment.